PENANGGULANGAN WANPRESTASI DI DALAM PERJANJIAN KARTU KREDIT (Jurnal De Jure Muhammadiyah Cirebon, 2024)
Default is a legal term derived from the Dutch language, namely "wanprestatie". This term is used in civil law to refer to a violation or negligence committed by one of the parties to the contract, which causes the non-fulfilment of the obligations agreed upon in the contract. Default can occur when one party does not fulfil its obligations in accordance with the terms set out in the contract, be it in the form of delay, not delivering the promised goods or services, or not doing something that should be done in accordance with the contents of the contract. In the case of default, the injured party can file a lawsuit to claim compensation or request the fulfilment of obligations in accordance with the contents of the contract.Keywords: Handling, default, agreement, credit card